Antithetical arts : on the ancient quarrel between literature and music - Kivy, Peter (Clarendon Press ; Oxford Univ. Press, 2009)
Peter Kivy presents a critical examination of the two rival ways of understanding instrumental music. He argues against 'literary' interpretation in terms of representational or narrative content, and defends musical formalism. He also discusses interpretations of a range of works in the canon.